2021
DOI: 10.1111/jpc.15419
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus subtype circulation and associated disease severity at an Australian paediatric referral hospital, 2014–2018

Abstract: Aim Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections in children and the development of vaccines to protect at‐risk groups is a global priority. The aim of this study was to describe RSV subtype circulation patterns and associated disease severity to inform on potential impact of an RSV‐specific prevention strategy. Methods Single‐centre retrospective observational study of children aged <16 years with laboratory‐confirmed RSV infection from 2014 to 2018 inclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In our cohort, clinical profiles of ON1-5-positive cases did not differ significantly from other ON1 lineages ( Supplementary Table 2 ). There have also been mixed reports on how RSV-A compares to RSV-B regarding virulence ( Martinello et al, 2002 ; Panayiotou et al, 2014 ; Midulla et al, 2019 ; Saravanos et al, 2021 ). Our analysis showed that fewer RSV-A ON1-5 infected patients presented “coarse breath sounds,” “shortness of breath” and were diagnosed with severe inflammation in the lungs compared to RSV-B infections ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, clinical profiles of ON1-5-positive cases did not differ significantly from other ON1 lineages ( Supplementary Table 2 ). There have also been mixed reports on how RSV-A compares to RSV-B regarding virulence ( Martinello et al, 2002 ; Panayiotou et al, 2014 ; Midulla et al, 2019 ; Saravanos et al, 2021 ). Our analysis showed that fewer RSV-A ON1-5 infected patients presented “coarse breath sounds,” “shortness of breath” and were diagnosed with severe inflammation in the lungs compared to RSV-B infections ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the initial curb of infections in 0-36-month-olds could have potentially resulted in this wave of RSV cases in late November/early December 2022 and increased hospitalisation rates, as also recorded by the US RSV Network (20, 21). The literature offers limited data on the severity and course of RSV infections in primary health care settings, as many studies have focused on the outpatient setting or hospitalised patients (2,10,11,21,22). In the first years of life, infants face a significant burden due to RSV in both inpatient and outpatient settings (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…As the virus evolves, new variants continuously develop while others disappear. Whether and to what extent the two RSV types influence seasonality, transmission rate, rate of co-infection, and severity of virus-associated disease is controversially discussed in the literature (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, children have a relatively rapid respiratory rate and are more vulnerable to respiratory diseases such as asthma, cough, and respiratory inflammation. Studies have shown that respiratory diseases have become the most frequent cause of childhood outpatient visits for illness, and these diseases are a primary medical problem adversely affecting the health and growth of children ( 40 ).…”
Section: Discussionmentioning
confidence: 99%